A escola como espaço de formação e a mediação da gestão escolar: o caso de uma escola da rede municipal de Presidente Prudente - Deák, Simone [UNESP] (2015)
This thesis was developed under the Postgraduate Program - Doctorate in Education of São Paulo State University (Unesp), School of Technology and Sciences, Presidente Prudente and linked to the research area called Public Policy, School Organization and Teacher Training. The focus of the study was on teacher training centered on the school, considering the continuous formative processes triggered from this space, which constitutes a place where teachers learn their profession. The general objective was the investigation, identification and analysis of managers' practices which trigger processes of teacher-centered continuing education and the specific ones were the identification and description of continuous teacher's formative practices and processes promoted by the managers, detecting which practices carried out interfere in the continuous formation of teachers, follow-up and analysis of the moments of continuous formation organized and proposed by the managers. Qualitative research in the case study modality was chosen and developed in a school in the Municipal Education Network of Presidente Prudente. The procedures adopted were documental analysis; observation of school-centered formative moments; interviews with the managers and teachers. In order to choose the school internal and external criteria were adopted, the first being the continuity of the managers in the school studied and the second, the result of the external evaluations and the performance of the schools of the municipality, considering that the selected school met these two criteria ... (Complete abstract click electronic access below)